The Influence of Village Fund Allocation (Add) On Community Welfare in Pantai Mekar Village, Muara Gembong District, Bekasi District - Rizki, Ferdy; Mulyadi, Andi; Fajar Basori, Yana (Lafadz Jaya Publisher, 2024)
Village Fund Allocation is one of the government budgets intended for village communities and managed by the Village Government. The aim of this research is to find out how much influence Village Fund Allocations have on the welfare of village communities in Bantargadung Village & to find out how much influence Village Fund Allocations have on the welfare of village communities in Pantai Mekar Village. The method used is the descriptive method, this method is used to take samples. The descriptive method focuses on collecting, presenting, processing and summarizing data. The sampling technique uses incidental sampling technique. Data collection methods using interviews and questionnaires. Data analysis uses simple linear regression analysis. The results of this research show in the T test that village fund allocation has a significant effect on the welfare of village communities because Tcount > Ttable, namely 7.123 > 166342 and the resulting significance is 0.00 < 0.05. This means that the village fund allocation variable has a significant influence on the welfare of village communities.